A KSHV RNA-binding protein promotes FOS to inhibit nuclease AEN and transactivate RGS2 for AKT phosphorylation - Vladimir Majerciak; Beatriz Alvarado-Hernandez; Yanping Ma; Shivalee Duduskar; Alexei Lobanov; Maggie Cam; Zhi-Ming Zheng (mBio)
ABSTRACT Kaposi’s sarcoma-associated herpesvirus (KSHV) encodes an RNA-binding protein ORF57 in lytic infection. Using an optimized CLIP-seq in this report, we identified ORF57-bound transcripts from 544 host protein-coding genes. By comparing with the RNA-seq profiles from BCBL-1 cells with latent and lytic KSHV infection and from HEK293T cells with and without ORF57 expression, we identified FOS RNA as one of the major ORF57-specific RNA targets. FOS dimerizes with JUN as a transcription factor AP-1 involved in cell proliferation, differentiation, and transformation. Knockout of the ORF57 gene from the KSHV genome led BAC16-iSLK cells incapable of FOS expression in KSHV lytic infection. The dysfunctional KSHV genome in FOS expression could be rescued by Lenti-ORF57 virus infection. ORF57 protein does not regulate FOS translation but binds to the 13-nt RNA motif near the FOS RNA 5′ end and prolongs FOS mRNA half-life 7.7 times longer than it is in the absence of ORF57. This binding of ORF57 to FOS RNA is likely competitive to the binding of host nuclease AEN (ISG20L1) of which physiological RNase activity remains unknown. KSHV infection inhibits the expression of AEN, but not exosomal RNA helicase MTR4. FOS expression mediated by ORF57 inhibits AEN transcription through FOS binding to AEN promoter but transactivates RGS2, a regulator of G-protein-coupled receptors. FOS binds a conserved AP-1 site in the RGS2 promoter and enhances RGS2 expression to phosphorylate AKT. Altogether, we have discovered that KSHV ORF57 specifically binds and stabilizes FOS RNA to increase FOS expression, thereby disturbing host gene expression and inducing pathogenesis during KSHV lytic infection.IMPORTANCEWe discovered that FOS, a heterodimer component of oncogenic transcription factor AP-1, is highly elevated in KSHV-infected cells by expression of a viral lytic RNA-binding protein, ORF57, which binds a 13-nt RNA motif near the FOS RNA 5′ end to prolong FOS RNA half-life. This binding of ORF57 to FOS RNA is competitive to the binding of host RNA destabilizer(s). KSHV infection inhibits expression of host nuclease AEN, but not MTR4. FOS inhibits AEN transcription by binding to the AEN promoter but transactivates RGS2 by binding to a conserved AP-1 site in the RGS2 promoter, thereby enhancing RGS2 expression and phosphorylation of AKT. Thus, KSHV lytic infection controls the expression of a subset of genes for signaling, cell cycle progression, and proliferation to potentially contribute to viral oncogenesis.